2016
DOI: 10.3390/molecules21101312
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Diseases: Might Citrus Flavonoids Play a Protective Role?

Abstract: Neurodegenerative diseases (ND) result from the gradual and progressive degeneration of the structure and function of the central nervous system or the peripheral nervous system or both. They are characterized by deterioration of neurons and/or myelin sheath, disruption of sensory information transmission and loss of movement control. There is no effective treatment for ND, and the drugs currently marketed are symptom-oriented, albeit with several side effects. Within the past decades, several natural remedies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 165 publications
0
65
0
Order By: Relevance
“…However, the increased employment of alternative and complementary medicines requires a lot of attention from the scientific community in order to evaluate the effectiveness and safety of herbal preparations since studies have cast some doubts on whether their use is really producing an alternative to synthetic drugs (5,36,37). Although numerous in vitro and in vivo studies have suggested a protective effect of green-tea polyphenols against development of prostate cancer, to date this has not been unequivocally demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased employment of alternative and complementary medicines requires a lot of attention from the scientific community in order to evaluate the effectiveness and safety of herbal preparations since studies have cast some doubts on whether their use is really producing an alternative to synthetic drugs (5,36,37). Although numerous in vitro and in vivo studies have suggested a protective effect of green-tea polyphenols against development of prostate cancer, to date this has not been unequivocally demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite bioavailability problems, numerous experimental and clinical data have demonstrated the ability of Citrus flavonoids to exert important systemic pharmacological effects [14,281,282]. In addition, Citrus flavonoids also display neuroprotective effects [283,284], suggesting that they are able to cross the blood–brain barrier. One explanation for the apparent discrepancy between the poor bioavailability of flavonoids and their biological activity in humans would be to assume that a significant part of the biological actions exhibited by Citrus flavonoids are due to their active metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Various citrus fruits have been found to contain abundant bioactive compounds that potentially provide benefits for human health . Numerous studies have focused on citrus flavonoids, including naringenin, hesperitin, nobiletin, and tangeretin, revealing their anti‐oxidative, anti‐cancer, anti‐inflammatory, cardiovascular‐protective, and neuro‐protective effects . After utilizing the pulps, citrus‐processing industries generate a lot of citrus peel waste.…”
Section: Introductionmentioning
confidence: 99%